Intensified rainfall seasonality and elevated nitrogen deposition reduce soil phosphorus availability in a subtropical forest: Linkages to functional microbes and enzyme kinetics - Zhiming Guo; Anna Gunina; Qingshui Yu; Jianbo Fang; Jinhong He; Xiuling Ni; Yanxia Nie; Xiaoge Han; Dan He; Muhammed Mustapha Ibrahim; Xiangping Tan; Weijun Shen (Applied Soil Ecology, 2026)

Season-dependent combined effects of nitrogen deposition and precipitation change on soil microbial communities and functions in a subtropical forest - Zhiming Guo; Jianbo Fang; Jinhong He; Xiuling Ni; Yanxia Nie; Xiaoge Han; Dan He; Xiangping Tan; Weijun Shen; Anna Gunina (Biology and Fertility of Soils, 2026)

Contrasting responses of rhizosphere microbial guild to nitrogen enrichment are associated with mycorrhizal plant type - Zhiming Guo; Xiuling Ni; Xiaomin Ma; Jianbo Fang; Jinhong He; Yanxia Nie; Xiangping Tan; Weijun Shen (Applied Soil Ecology, 2026)

Multi-level cognitive state classification of learners using complex brain networks and interpretable machine learning - Xiuling He; Yue Li; Xiong Xiao; Yingting Li; Jing Fang; Ruijie Zhou (Cognitive Neurodynamics, 2025)

Accelerating peroxymonosulfate activation over fiber-shaped Fe@Fe3C/CNF for ultrafast tetracyclines degradation: Active site synergy and mechanisms - Man Yang; Yafan Lu; Wenjuan Zhang; Long Xie; Junjie Tian; Yiliyasi Baikeli; Fang Wang; Yong-Zheng Zhang; Da-Shuai Zhang; Xiuling Zhang; Mika Sillanpää; Longlong Geng (Journal of Environmental Chemical Engineering, 2024)

Seed Endophytes and Their Roles in Host Plant Stress Resistance - Wenqin Mao; Yuanshuang Wu; Fang Li; Wenting Tang; Weijun Gong; Xue Han; James F. White; Xiuling Ji; Haiyan Li (Journal of Soil Science and Plant Nutrition, 2023)

A rapid and effective method for obtaining ardicrenin from Ardisia crenata Sims var. bicolor plants - Zhen Lin; Xiuling Yang; Lin Li; Chunyan Ma; Lingjuan Kong; Huancheng Li; Shican Xiong; Haiyan Zhong; Shangrao Pu; Fang Liang; Ju Hu (Brazilian Journal of Botany, 2023)

Facile one-pot synthesis of multifunctional tetracycline hydrochloride nanoparticles with high stability and photothermal effect for synergistically improved antibacterial performance and sustainability - Mingzhou Lu; Weitao Wang; Xiuling Fang; Yang Xuan; Liying Chen; Xiaojing Wang; Jianhao Wang; Cheng Wang (Sustainable Chemistry and Pharmacy, 2023)

Improved spring temperature reconstruction using earlywood blue intensity in southeastern China - Xinguang Cao; Hongbing Hu; Pei‐ken Kao; Brendan M. Buckley; Zhipeng Dong; Xiuling Chen; Feifei Zhou; Keyan Fang (International Journal of Climatology, 2022)
Because instrumental observations are too short to fully represent long‐term natural variability, high‐resolution temperature proxy records are essential to understanding past climate and assessing current climate variability in the context of long‐term patterns. In the subtropics, progress in this field has been hampered by a relative lack of long and truly temperature‐sensitive proxy records. In this study, we provide an assessment of the dendroclimatic potential of blue intensity (BI) and ring‐width (RW) measurements from two hot/humid Pinus massoniana sites in China. Our results show that RW exhibits a significant ( p

Chemical constituents from Glehnia littoralis and their chemotaxonomic significance - Shouwen Zhang; Fang Cheng; Li Yang; Jinxiang Zeng; Fengyu Han; Xiuling Yu; Yuye Zhu; Guoyue Zhong; Junwei He (Natural Product Research, 2020)

Fine-mapping qFS07.1 controlling fiber strength in upland cotton (Gossypium hirsutum L.) - Xiaomei Fang; Xueying Liu; Xiaoqin Wang; Wenwen Wang; Dexin Liu; Jian Zhang; Dajun Liu; Zhonghua Teng; Zhaoyun Tan; Fang Liu; Fengjiao Zhang; Maochao Jiang; et al. (Theoretical and Applied Genetics, 2017)

Complete genome sequence of the cold-active bacteriophage VMY22 from Bacillus cereus - Kunhao Qin; Benxu Cheng; Shengting Zhang; Nan Wang; Yuan Fang; Qi Zhang; Anxiu Kuang; Lianbing Lin; Xiuling Ji; Yunlin Wei (Virus Genes, 2016)

Developing drainage as the basis of comprehensive control of drought, waterlogging, salinity and saline groundwater - Fang Sheng; Chen Xiuling (Irrigation and Drainage, 2007)